Cardiac Myxoma- Surgical treatment and outcome - Reddy, D Jaypal; Sah, Bijay (Journal of College of Medical Sciences-Nepal, 2015)
Background & Objectives: Cardiac Myxomas include benign and malignant neoplasms, arising within the cardiac chambers or in the myocardium. Because, it is a rare tumor of the heart, there seems a lack of adequate data and its recent optimal treatment for both benign and malignant tumors is limited. Materials & Methods: Literature was searched for review and prospective study of cardiac myxoma surgery done between August 1990 and February 1996 was presented. A total of six patients underwent surgery for cardiac myxoma. All patients (five female; one male) underwent complete excision of the tumor and none of them showed features of remission after six month follow-up. Results: Cardiac Myxoma is a rare disease and it most commonly occurs in the fourth decade of life. Out of six patients operated, five were female and one was male and the age of the patients was between 22 and 50 years (mean age 31). The location of tumors was: LA myxoma in five cases, RA myxoma in one case. Preoperative symptoms were dyspnea (NYHA class III) in four cases, orthopnea in two cases, postural giddiness or syncope in three cases, palpitation in two cases and chest pain in two cases. The mean duration of onset of symptoms to diagnosis was eight months. Echocardiography showed abnormalities in all six cases including mitral stenosis in five cases, and tricuspid stenosis in one case. No recurrence was noted after six months of follow-up after the surgery. Conclusion: Cardiac myxoma is considered an emergency condition which needs urgent procedure, particularly if the patient has a history of embolism or syncope. Atrial Myxoma tends to have more secondary scenarios by embolization. JCMS Nepal. 2015; 11(2):27-30